Negative Phenomena Resulting from Social Events in Libyan Society (Comprehensive Journal of Science, 2026)
The current research aims to identify the negative effects of social events on individuals, families, society, and neighbors. These effects cause harm, anxiety, and disturbance, and lead to psychological pressure and discomfort for various groups (infants, students, employees, the sick, and the elderly). These negative impacts are a result of the behavior of some individuals who act outside the law, demonstrating poor morals and a lack of respect for others. Such actions are condemned by Islamic law and punishable by civil law.Also, the absence of competent regulatory and security authorities that organize, control, and fine those who violate the system and the law to limit its spread within society – as the first section reviewed the negative phenomena left by social events, and the second section discussed the effects on neighbors due to these negative phenomena.
Keywords: Negative Phenomena, Social Events, Competent Authorities, the Law.